Total Phenolic Contents and Antioxidant Activities of Olive (Olea europaea L.) Pomace and Their Ingredients - Rathi, Munther Hamza; Turki, Russl Hassan (Al-Nahrain Journal of Science, 2018)
In this study, the determination of total phenolic and antioxidant activity of the wastes of Olea europaea L. wastes was determined obtained from the process of pressing and extraction of oil from the fruits of O. europaea L. which are peels, seeds and pomace (peels and seeds). Five solvents where used in the extraction process to identify the best method for the extraction. The results of the present study showed that the type of solvent in the extraction process and the selected part of the waste have important role in determining of phenolic compounds as well as antioxidant activity of the pomace, peels and seeds. Hydroethanolic extracts (50% water) was the best in phenolic compounds extraction comparison with other solvents (water at room temperature, boiling distilled water and hydrochloric acid diluted with distilled water by (1% and 5%). In contrast, extracts from the pomace, peels and seeds using 5% hydrochloric acid had higher antioxidant activity through their ability to inhibit the activity of the synthetic free radical DPPH (2.2-diphenyl-1-pcriylhydrazal) when compared with other solvents. The extracts of peels showed significantly higher (P ≤ 0.05) amounts of the phenolic compounds and the antiradical activity against DPPH than those prepared from the pomace and seeds.